2021
DOI: 10.1098/rstb.2020.0207
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy, family constellation and stress in giant mole-rats ( Fukomys mechowii )

Abstract: Giant mole-rats ( Fukomys mechowii ) are remarkably long-lived subterranean rodents (maximum recorded lifespan as reported here greater than 26 years) that live in families with one reproductive pair (breeders) and their non-reproductive offspring (non-breeders). Previous studies have shown that breeders live on average approximately twice as long as non-breeders, a finding contradicting the classic trade-off between reproduction and lifespan. Because recent evidence points to the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…A role for peroxiredoxins also became evident in several other transcriptome studies in this volume [30,32,33]. Furthermore, Quigley & Amdam [49] also stress the importance of social interactions in modulating senescence in humans, similar to what has been shown in social insects and social rodents [33,40,43,46,47].…”
Section: Contributionsmentioning
confidence: 58%
“…A role for peroxiredoxins also became evident in several other transcriptome studies in this volume [30,32,33]. Furthermore, Quigley & Amdam [49] also stress the importance of social interactions in modulating senescence in humans, similar to what has been shown in social insects and social rodents [33,40,43,46,47].…”
Section: Contributionsmentioning
confidence: 58%
“…However, current evidence suggests that Fukomys indeed exhibits strict social and predominant sexual monogamy, the latter fluctuating in frequency between populations (Burland et al, 2002;Patzenhauerová et al, 2013). While staying faithful to their current mate for prolonged periods (Bappert et al, 2012;Begall et al, 2021), Fukomys may experience serial changes in partners over their lifetime (Burland et al, 2002;Šumbera et al, 2012;Patzenhauerová et al, 2013). Different mating systems are expressed in the other two social bathyergid genera.…”
Section: Introductionmentioning
confidence: 95%
“…Altered MC2R expression ( Fig. 6A) coincides with higher cortisol levels in hair samples from non-breeding F. mechowii than in those from breeders of the same species (Begall et al 2020). Furthermore, glucocorticoids such as cortisol exert their effect by binding to the glucocorticoid receptor that, in turn, acts as a transcription factor for many genes (Gjerstad et al 2018).…”
Section: Resultsmentioning
confidence: 95%
“…Nevertheless, a recent study confirmed one of the most important predictions of the hypothesis: hair cortisol levels of non-breeders are on average about twice as high as those of breeders. However, a subgroup of non-breeders, defined by social environmental factor (one or both parents had died), exhibited cortisol levels nearly as low as in breeders (Begall et al 2020). The drop of cortisol levels in orphaned non-breeders is accompanied by a substantial drop of mortality rates in this subgroup approaching the values of breeders ( Figure 6-figure supplement 1).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation